PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN (AMDK) MEREK AQUA (STUDI PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS RIAU) - Ningsih, Fitria; Nas, Sakdanur; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aimed to determine of product quality and price toward the purchase decision bottled water brand Aqua to Economic Education Student of Riau University. The research was conducted at the Economic Education of Riau University. The populations in this study are economic education students generation 2013-2015 numbered 256 people. The samples was taken with proportionate stratified random sampling. The number of the sample was 72 people. The data analysis technique was used multiple regression. The results of this study showed that: 1) Product quality significantly to the influence purchase decisions of bottled water brand Aqua to Economic Education Student of Riau University. 2) Price do not significantly to the influence purchase decisions of bottled water brand Aqua to Economic Education Student of Riau University.Key Words: Product Quality, Price, Purchase Decisions